Liquidity shocks, commodity financialization, and market comovements. Issue 9 (15th May 2020) - Hu, Conghui; Li, Zhibing; Liu, Xiaoyu
Abstract: We explore whether and how liquidity factors influence risk transfers between commodity and stock markets using a composite liquidity index and five different types of liquidity measures. We find that liquidity shocks, including both funding liquidity and market liquidity, are positively associated with comovements between commodity and stock markets after 2000, although the relationship is insignificant before 2000. The structural change indicates that financialization creates a role for adverse liquidity shocks to increase cross‐market correlations. Further evidence shows that the effect of liquidity on cross‐market correlations is state‐dependent and intensifies when liquidity conditions deteriorate and asset returns sustain substantial declines. Our findings are not explained by business cycles.